A homogeneous ethanedithiol doped ZnO electron transporting layer for polymer solar cells. Issue 37 (5th September 2016) - Yang, Hanjun; Wu, Ting; Hu, Ting; Hu, Xiaotian; Chen, Lie; Chen, Yiwang
Abstract : In situ grown ZnO doped with EDT was employed to improve the performance of inverted polymer solar cells. Abstract : A 1, 2-ethanedithiol (EDT) doped ZnO (ZnO@EDT) composite prepared by a facile and general approach was developed as an electron transporting layer to improve the performance of inverted polymer solar cells. The strong interaction between ZnO and the –SH group of EDT contributes to the formation of a homogeneous film of ZnO@EDT. Meanwhile, EDT could passivate the surface defects and increase the electron mobility of ZnO effectively. Compared to bare ZnO, ZnO@EDT could increase electron extraction and facilitate photoinduced carrier generation. As a result, the inverted polymer solar cell based on thieno[3, 4- b ]thiophene/benzodithiophene (PTB7):[6, 6]-phenyl C71 -butyric acid methyl ester (PC71 BM) with ZnO@EDT as an electron transporting layer delivered an enhanced PCE of 8.0%.